Heterologous Immune Responses of Serum IgG and Secretory IgA Against the Spike Protein of Endemic Coronaviruses During Severe COVID-19 - Smit, Wouter L.; van Tol, Sophie; Wal, Sanne van der; van Vulpen, Femke; la Grouw, Shannon; van Lelyveld, Lenneke; Limonard, Gijs; Bossink, Ailko; Godeke, Gert-Jan; Shrestha, Sandhya; Reimerink, Johan; Eggink, Dirk; et al. (Frontiers in Immunology, 2022)
Defining immune correlates of disease severity is important to better understand the immunopathogenesis in COVID-19. Here we made use of a protein microarray platform to detect IgG- and IgA-reactive antibodies in sera and saliva respectively, and assess cross-reactivity between SARS-CoV-2 and endemic coronaviruses (eCoVs). IgG responses against the full protein of spike, but not the S1 subunit, were significantly higher in convalescent sera of patients with severe disease compared to mild disease and healthy controls. In addition, we detected reactivity of secretory IgA to eCoVs in saliva of patients with severe disease, not present in moderate disease or seropositive healthy controls. These heterologous immune responses are in line with non-protective cross-reactivity, and support a potential role for immune imprinting in the pathogenesis of severe COVID-19.